Na calada da noite: silêncio - Reis, Priscila Loureiro (2017)
To think of the pronounced saying of music is to walk the paths that unify thought, listening and meaning. To think of music as the inaugural constitution of the world, and therefore, the generator of meaning, is to conceive it together with the emergence of the real that takes place in the event of truth as a veiling of revelation. The articulation of music with this tension of recollection and announcement takes place in unity with silence: condition of possibilities and possibilities of a listening that auscultates language in the care of attending and corresponding to the vital imperative of an inaugural speech. It is the appeal offered by the real in the search of man for the sense of being. In the dead of night the man is faced with his finitude and decides to reject all the dictates imposed by the culture of technical-scientific functionality that tries to increasingly automate, homogenize and standardize world views and visions. Awakened to a mysterious reality that has never been absent, man can be enchanted by the poetic word spoken by the voice of the muses, the children and the poets, listening at night to the musicality of the silence that composes the being. The methodology chosen for the development of this work was the hermeneutic phenomenology in dialogue mainly with the thought of Martin Heidegger.